Case Report: Upper Thoracic Purely Extradural Spinal Meningioma With Nerve Root Attachment: A Case Report and Literature Review - Wang, Zhao-Lin; Mou, Jian-Hui; Sun, Dong; Liu, Peng (Frontiers in Surgery, 2022)
Introduction We describe a case of purely extradural spinal meningioma (EDSMs) with nerve root attachment and present the clinical profiles, radiological findings, operative management, and follow-up data, along with a literature review. This case study is purely extradural spinal meningioma attached to the nerve root, and the available literature review discusses the diagnosis and treatment. Purely epidural spinal meningiomas are extremely rare, and only a few clinical reports are published on this disease. Although epidural meningioma is a benign tumor, the recurrence rate is higher when compared with ordinary meningioma. Case study A 39-year-old male complained of chest and back pain with ring-shaped radiations to the precordial area and numbness in both the lower extremities. After a long walk, he felt disharmony in both his lower limbs. Magnetic resonance imaging showed a mass located on the left posterolateral side of the T1–T3 spinal cord and exhibited a dumbbell-type growth outward at the level of the T2–T3 intervertebral foramen. On the left side of the thoracic, a hemilaminectomy procedure was performed. The tumor was found in the ventral side of the left nerve root of T1 and was surrounded by the left nerve root of T2. To obliterate the tumor, the T2 nerve root was severed. The patient was advised to come for the follow-up on the 3rd, 6th, and 12th months postoperatively, and there were no complaints or signs of recurrence. Conclusion Purely extradural spinal meningioma with nerve root attachment is rare and has no clinical symptoms and image findings. To completely resect the lesion and avoid recurrence, the affected nerve root, epidural fat tissue, and nerve root sheath should be extensively resected and burned, coagulating the adjacent ventral posterior longitudinal ligament.